Cassava cultivation in Asia - Maung Aye, Tin (Burleigh Dodds Science Publishing Limited, 2017)
Cassava was introduced to Asia in the late eighteenth and the early nineteents centuries. Since then it has become one of the most popular crops, especially in upland environments. Cambodia, Indonesia, Thailand and Vietnam are now among the top producers and exporters of cassava in the world. This chapter provides an overview of cassava production in Asia, and then reviews some of the key areas of research for developing cassava production, including varietal improvement, crop management techniques, planting and harvesting, soil fertility maintenance and pest, disease and weed control. Finally, a case study on the development of sustainable cassava production in Cambodia is provided.